Pengaruh Latihan Lunges Terhadap Akurasi Shooting Dalam Keterampilan Futsal Pada Siswa SD - Mahendra, Reza Rizky; Safari, Indra; Ahmad Fauzi, Rizal (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to determine the effect of lunges training on futsal shooting accuracy in elementary school students and whether there is an increase after following the training program. The method used is a quasi-experiment with a